A Study on Performance Appraisal - K. Ravi Kiran Yasaswi; Ch. D. V. Sai Kumar; D. Bharath Lakshman; T. Jaswanth (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The human workforce behavior estimated with the help of performance appraisal through perception analysis of human resource management using working behavior metrics through gauge the employees in the technology generation.